State Civil Service Placement System (ASN) through Analysis based Selection (BERLIAN) in the Government of Gorontalo Regency - Rafif Rabbani; Ismet Sulila; Rizal (LP2M Universitas Bina Mandiri Gorontalo, 2021)
The objectives of this study are: 1) knowing and analyzing the process of placing state civil servants through an analysis-based selection of positions within the Gorontalo District government; 2) knowing and analyzing the determining factors in the process of placing state civil servants through an analysis-based selection of positions within the government. Gorontalo District. This research is a research with a qualitative descriptive approach, namely examining, analyzing and decrypting data. Results of the study: 1) the system of placing state civil servants through a selection based on job analysis in the Gorontalo District government is seen from the placement in one SKPD has been implemented properly, however, there are still some ASN who still have limitations in terms of expertise and skills in positions that are held. just occupied. Judging from the placement between SKPD has been carried out in accordance with the process, however, there are several ASN that have not met the requirements to be transferred. Furthermore, from the point of view that moving in and out of the region has been running according to the provisions, but it does require a fairly long process and takes quite a long time; 2) the determining factors in the placement of ASN are: Education, Work Experience, Work Knowledge, Work Skills.